2019
DOI: 10.1155/2019/5984804
|View full text |Cite
|
Sign up to set email alerts
|

Experiment Investigation and Numerical Simulation of Snowdrift on a Typical Large‐Span Retractable Roof

Abstract: Retractable roofs are commonly used in designing large-span stadiums because of their versatility. However, retractable roofs are subject to sudden changes in shape, and thus, factors in addition to those considered for conventional roofs need to be taken into account. In particular, retractable roofs are considerably more sensitive to snow loads because their shapes are complex, and snowdrift on roofs may lead to difficulties for the operating of retractable roofs. To investigate the distribution of snow on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…e static analysis is mainly used to analyze the deformation and equivalent stress of the chassis after being loaded. According to the value of the total variables and the equivalent stress on the cloud map, the bearing capacity of each part of the chassis is analyzed [32]. Based on the previous meshing, loading and restraining of the chassis frame, the stress-strain cloud map is obtained as Figure 5.…”
Section: Stress and Strain Analysis Of The Chassis Framementioning
confidence: 99%
“…e static analysis is mainly used to analyze the deformation and equivalent stress of the chassis after being loaded. According to the value of the total variables and the equivalent stress on the cloud map, the bearing capacity of each part of the chassis is analyzed [32]. Based on the previous meshing, loading and restraining of the chassis frame, the stress-strain cloud map is obtained as Figure 5.…”
Section: Stress and Strain Analysis Of The Chassis Framementioning
confidence: 99%
“…However, it is challenging to conduct precise quantitative research for the railway lines passing through areas prone to wind and snow disasters or sparsely populated Gobi areas, mainly due to the large accidental errors and low reproducibility of measurement and the presence of many uncontrollable external factors (Tominaga, 2018). Researchers have widely recognized wind tunnel tests due to the advantages of controllable environmental variables and systematic parametric measurement (Cao et al, 2019;Kumar et al, 2020). Wind tunnel tests allow scaling building entities by adopting granular materials with different properties and performing calculations according to the similarity criterion (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al carried out an experiment and numerical study on snowdrift on a typical large-span retractable roof utilizing the Euler-Euler technique. It was revealed that not one unchanging snow delivery on the roofs was different, which must be well thoughtout [23]. Other researchers also researched the various turbines for power generation, axial flow pumps, and energy conservation.…”
Section: Introductionmentioning
confidence: 99%